Philosophical perspectives on art - Davies, Stephen (Oxford University Press, 2007)
Philosophical Perspectives on Art presents a series of essays devoted to two of the most fundamental topics in the philosophy of art: the distinctive character of artworks and what is involved in understanding them as art. In Part I, Stephen Davies considers a wide range of questions about the nature and definition of art. Can art be defined, and if so, which definitions are the most plausible? Do we make and consume art because there are evolutionary advantages to doing so? Has art completed the mission that guided its earlier historical development, and if so, what is to become of it now? Should architecture be classified as an art form